A Bird-Finding Guide to Ontario. - Goodwin, Clive E. (University of Toronto Press, 1995)
From southern deciduous woodlands to Arctic coastline, this guide presents precise directions on where birds are found, emphasizing the most popular and productive localities, but also citing numerous little-known locales that will delight aficionado and novice alike.